Beplanning by stedelike agteruitgang en stedelike hernuwing: Batho as moontlike presidentsprojek - Van der Merwe, Daniel Paul (University of the Free State, 2002)
Abstract not availalbe
Dissertation (M.U.R.P. (Urban and Regional Planning))--University of the Free State, 2002
Keywords: City planning -- South Africa -- Batho (Bloemfontein)